ANTI - INFLAMMATORY ACTIVITY OF FLOWERS OF NYMPHAEA ALBA BY HRBC MEMBRANE STABILIZATION METHOD - Karthikeyan, Ramadoss (Research in Plant Biology, 2015)
Ã‚Â Object: To evaluate the anti inflammatory activity from the flowers of Nymphaea alba. Methods: Human red blood cell membrane stabilization (HRBC method) has been used as a method in estimating the anti inflammatory property of Nymphaea alba flowers. Results: Acute oral toxicity study. The extracts of Nymphaea alba did not show any sign of toxicity up to 2000 mg/ml body weight and hence it was considered to be safe. The in vitro method showed significant anti inflammatory property of different concentrations tested. Conclusion: The hydroalcoholic extract at a concentration of 500ÃŽÂ¼g/ml showed significant activity when compared with the standard control ibuprofen.